IMPLEMENTATION OF THE AUCTION PROCESS SYSTEM AT THE CITY STATE ASSETS AND AUCTION SERVICE OFFICE (KPKNL) PAREPARE - Rosdiana Rosdiana; Mukmin Muhammad (Jurnal Scientia, 2023)
This research is a qualitative research with a sociological juridical approach to determine the implementation of auctions. This research took place at the State Property and Auction Service Office (KPKNL) in Parepare City. Interviews were conducted with informants, resource persons and respondents to find out about the implementation of the auction at the Parepare KPKNL. The analysis took place interactively by starting from question and answer activities with structured questions, data collection, data presentation and conclusions or verification. The results of the study show that the implementation of the auction by the Parepare KPKNL is in accordance with the Minister of Finance Regulation No. 93/PMK.06/2010 concerning Guidelines for Auction Implementation, and the theory of Good Governance, but there are still obstacles, namely community members who do not know about the functions of the KPKNL, and how to participate in auctions. The author's suggestion to the State Property Service Office and Parepare Auctions is to further increase the intensity of communication with the public so that the public does not hesitate to participate in auction activities held by the KPKNL.